Safety and efficacy of a feed additive consisting of an essential oil from the gum resin of Ferula assa‐foetida L. (asafoetida oil) for use in dogs and cats (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal, 2022)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of an essential oil obtained from gum resin of Ferula assa‐foetida L. (asafoetida oil), when used as a sensory additive (flavouring) in feed for dogs and cats. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the use of asafoetida oil is safe at the proposed conditions of use of 1.5 mg/kg complete feed for dogs and 0.2 mg/kg complete feed for cats. The additive under assessment should be considered as irritant to skin and eyes, and as a dermal and respiratory sensitiser. Since F. assa‐foetida and its preparations are recognised to flavour food, and its function in feed would be essentially the same as that in food, no further demonstration of efficacy was considered necessary.